Medicare Part D: Are Insurers Gaming the Low Income Subsidy Design? - Decarolis, Francesco (American Economic Review, 2015)
This paper shows how in Medicare Part D insurers' gaming of the subsidy paid to low-income enrollees distorts premiums and raises the program cost. Using plan-level data from the first five years of the program, I find multiple instances of pricing strategy distortions for the largest insurers. Instrumental variable estimates indicate that the changes in a concentration index measuring the manipulability of the subsidy can explain a large share of the premium growth observed between 2006 and 2011. Removing this distortion could reduce the cost of the program without worsening consumer welfare.